Adapting Triandis's Model of Subjective Culture and Social Behavior Relations to Consumer Behavior - Lee, Julie Anne (Journal of Consumer Psychology, 2000)
This article develops and tests a framework for the investigation of cultural influences on consumer purchasing behavior by examining the psychological processes that intervene. The model is empirically tested with a camera purchase decision survey in Singapore, Korea, Hong Kong, Australia, and the United States. The data analyzed at the pooled, cultural, and individual difference (i.e., idiocentrism and allocentrism) levels supports the etic nature of the model. In addition, the theory of individualism (idiocentrism) and collectivism (allocentrism) was applied to the model to derive and test specific cross‐cultural hypotheses, including the impact of referent past experience and referent expectations and affordability on purchase intentions. At the individual level, it was found that both referent influences and affordability had a stronger influence for the allocentric subsample than for the idiocentric subsample.